Analisis Kebijakan Pembelajaran Tatap Muka di Masa Pandemi Covid-19 - Guliga, Baso; Fachry, Zul; Rachmat, Zul; Fadli, Zul (Jurnal Publik, 2022)
The government seeks to improve the quality of education during the Covid-19 pandemic based on the policy of the Joint Decree (SKB) of the Four Ministers concerning Guidelines for the Implementation of Face-to-face Learning during the Covid-19 Pandemic as an effort to save the nation's generation from loss of learning due to online learning which is considered ineffective. The Wajo Regency Education and Culture Office has held face-to-face learning starting on September 6, 2021. Based on verification according to the results of checking from the Covid-19 task force. In fact, the Dikbud of Wajo Regency can be quickly confirmed on the target object of the policy well, the policy implementing resources utilize the authority, facilities and infrastructure including budgeting in helping the community obtain basic rights through learning practices and health services. Through disposition, the involvement of all structural and functional bureaucrats as well as stakeholders has been running in a conducive manner. The result of this research is the implementation of the Face-to-Face Learning Policy during the Covid-19 Pandemic by the Dikbud of Wajo Regency, although it still requires continuous evaluation and supervision so that the policy continues until it enters a full transition period.